Three new species of Agaricus section Minores from China - M. Q. He (2018)
© 2018, Guizhou Academy of Agricultural Sciences. Agaricus subgenus Minores section Minores has the richest species in the genus Agaricus and worldwide distribution. In this paper, the phylogenetic trees generated by Maximum Likelihood and Bayesian analyses for section Minores were conducted using ITS, LSU and tef1-a genes sequences from 105 species. The molecular phylogenetic analysis showed there were three new lineages from Chinese specimens within this section, and the following morphological examination supported them as three new species. We named them as A. parvibrunneus, A. pseudominipurpureus and A. yanzhiensis respectively. Descriptions, colour photographs and illustrations of those new species are presented in detail.